2016
DOI: 10.19082/2355
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Surface Hardness of Various Shades of Twinky Star Colored Compomer Light-cured with QTH and LED Units

Abstract: IntroductionColored compomers are a group of restorative materials that were introduced in 2002 to repair primary teeth, and they provide attractive color and ease of use in pediatric dentistry. The aim of this study was to evaluate the effect of QTH and LED light-curing units on the surface hardness of different colors of Twinky Star compomers.MethodsIn this experimental study, a composite resin (Z250, 3M, and USA), an ionosit compomer (DMG, Germany) with A3 shade and 8 different Twinky Star colored compomer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 17 publications
2
9
0
4
Order By: Relevance
“…Other studies suggested that differently colored compomers might have different proportions of glittering components, causing different hardness values. 17, 28 This suggestion may also explain the effect of including pigments on the depth of curing, resulting in a change in the hardness values of the material; thus, the silver-colored compomer samples had the highest Vickers hardness number in our study.…”
Section: Discussionmentioning
confidence: 54%
“…Other studies suggested that differently colored compomers might have different proportions of glittering components, causing different hardness values. 17, 28 This suggestion may also explain the effect of including pigments on the depth of curing, resulting in a change in the hardness values of the material; thus, the silver-colored compomer samples had the highest Vickers hardness number in our study.…”
Section: Discussionmentioning
confidence: 54%
“…32 On the other hand, other studies reported better polymerization with darker materials compared to lighter counterparts. [33][34][35] The Grēngloo™ Adhesive is a green paste with a colorchange property that changes its color to a translucent color when the adhesive increases to warmer body temperatures. This feature allows easier removal of excess adhesive flash during bracket bonding before curing and facilitates cleanup of the adhesive remnants after debonding once the adhesive is cooled with air or water.…”
Section: Discussionmentioning
confidence: 99%
“…Çalışmamızda kullanılan farklı renklerdeki kompomerlerin formülasyonları aynı olduğu için polimerizasyon farklılıkları, farklı renkler için ihtiva ettikleri pigmentlerin türü ve miktarından kaynaklanıyor olabilir. 19 Üretici, twinky star ve glasiosite birleşiminin geleneksel kompomerlere benzediğini ve aralarındaki tek farkın yapıya eklenen pigmentler olduğunu belirtmiştir. Yüzey sertliğinin farklı renklerde değişmesi, pigmentlerin organik ya da inorganik olmasına ya da ışığın farklı renkler de farklı miktarda emilmesine bağlı olabilir.…”
Section: Discussionunclassified